The complete chloroplast genome of Isodon rubescens, a traditional Chinese herb - Zhiyong Yue; Yan Wang; Baozhen Zhou; Hanping Wang (Mitochondrial DNA. Part B. Resources, 2021)
Isodon rubescens (Hemsley) H. Hara is a kind of traditional medical herb which can be used for cancer treatment. In this study, the complete chloroplast genome sequence of I. rubescens was assembled. Its complete circular chloroplast DNA length was 152,761 bp. The genome was made up of a large single-copy region of 83,655 bp, a small single-copy region of 17,660 bp, and a pair of inverted repeat regions of 25,723 bp. The genome totally encoded 129 genes, containing 85 protein-coding genes, 36 tRNA genes, and eight rRNA genes. Phylogenetic analysis indicated that I. rubescens had a close relationship with basil (Ocimum basilicum).